Analysis of related rates of increase in PT. Singa Asia Perkasa Utama - Putri, Syaprina Mega; Sari, Purwita (Institute of Computer Science (IOCS), 2024)
The aim of this study is to see and understand how PT. Singa Asia Perkasa Utama report Value Added Tax, to look at and understand the problems faced by PT. Singa Asia Perkasa Utama, and to learn about the efforts made by PT. Singa Asia Perkasa Utama to report Value Added Tax. This study found that Value Added Tax report PT. Singa Asia Perkasa Utama in accordance with taxation laws. This research was conducted because this company has never been researched before on taxation issues, especially value added tax. Researchers want to know whether the reporting and collection of value added tax is done correctly and in accordance with the law. This study using methods such as interviews, observations, or observations and documentation. The Nvivo application, which is used in this study, is the NVivo 12 Plus. The company uses the VAT rate in accordance with the provisions already set out in the Act.